OPPORTUNITIES TO INDIVIDUALIZE THE PROCESS OF CONTINUOUS PROFESSIONAL DEVELOPMENT OF TEACHERS (American Journal of Interdisciplinary Research and Development, 2023)
The effectiveness of the system of continuous professional development of pedagogues depends on the extent to which their professional difficulties and needs are satisfied and their individual characteristics are taken into account. For this purpose, serious efforts are being made to introduce technologies aimed at ensuring the addressability and continuity of continuous professional development of pedagogues into the system.